Age Related Response of Neonatal Rat Retinal Ganglion Cells to Reduced TrkB Signaling in vitro and in vivo - Beros, Jamie; Rodger, Jennifer; Harvey, Alan R (Frontiers in Cell and Developmental Biology, 2021)
During development of retinofugal pathways there is naturally occurring cell death of at least 50% of retinal ganglion cells (RGCs). In rats, RGC death occurs over a protracted pre- and early postnatal period, the timing linked to the onset of axonal ingrowth into central visual targets. Gene expression studies suggest that developing RGCs switch from local to target-derived neurotrophic support during this innervation phase. Here we investigated, in vitro and in vivo, how RGC birthdate affects the timing of the transition from intra-retinal to target-derived neurotrophin dependence. RGCs were pre-labelled with 5’Bromo 2’Deoxyuridine (BrdU) at embryonic (E) day 15 or 18. For in vitro studies, RGCs were purified from postnatal day 1 (P1) rat pups and cultured in the presence or absence of: (i) brain derived neurotrophic factor (BDNF), (ii) blocking antibodies to BDNF and neurotrophin 4/5 (NT-4/5), or (iii) a tropomyosin receptor kinase B fusion protein (TrkB-Fc). RGC viability was quantified 24hr and 48hr after plating. By 48hr, the survival of purified βIII-tubulin immunopositive E15 but not E18 RGCs was dependent on addition of BDNF to the culture medium. For E18 RGCs, in the absence of exogenous BDNF, blockade of TrkB receptors using the two antibodies or TrkB-Fc reduced RGC viability at both 24hr and 48hr. Each blocking method also reduced complex process expression in surviving RGCs. In vivo, survival of BrdU and Brn3a co-labelled E15 or E18 RGCs was quantified in rats 24hr after P1 or P5 injection into the eye or contralateral superior colliculus (SC) of BDNF and NT-4/5 antibodies, or serum vehicle. The density of E15 RGCs 24hr after P1 or P5 injection of blocking antibodies was reduced after SC but not intraretinal injection. Antibody injections into either site had little obvious impact on viability of the smaller number of E18 RGCs. In summary, most early postnatal RGC death in the rat involves the elimination of early-born RGCs. The survival of early-born RGCs during this time is dependent primarily upon the availability of target derived BDNF, whereas late-born RGC survival may be influenced by additional factors, suggesting a relationship between RGC birthdate and developmental death mechanisms.